Phthalocyanine films as active layers of optical sensors for pentachlorophenol and simazine detection - Hassan, Aseel; Basova, Tamara; Tuncel, Sinem; Yüksel, Fatma; Gürek, Ayşe Gül; Ahsen, Vefa (Elsevier Science Bv, 2011)
Thin films of different nickel phthalocyanine derivatives (NiPcR8, with R= -NHSO2(C6H4) CH3, -CH2N(SO2C6H5-CH3)CH2(CH2)(8) CH3 and -NHCOCH2(CH2)(9)CH3) have been prepared by spin coating onto gold-coated slides and applied as active layers for the detection of pentachlorophenol (PCP) and semazine using Total Internal Reflection Ellipsometry (TIRE) technique. Solutions of pentachlorophenol and semazine in deionized water with different concentrations in the range 0.5-20 mu g/l were used in the current study. It was demonstrated that PCP with minimum concentration of 0.70 mu g/l could be detected with clear recovery in the Delta(lambda) spectra on flushing the cell with deionized water. Simazine on the other hand has resulted in an irreversible response on all three derivatives of NiPcR8 active layers used in this study, with the minimum determined concentration of 1 mu g/l in water. It has been demonstrated that the method used in this work has improved sensitivity over other methods such as surface Plasmon resonance. (C) 2011 Published by Elsevier Ltd.
25th Eurosensors Conference -- SEP 04-07, 2011 -- Athens, GREECE
Keywords: Phthalocyanine thin films; Optical detection; TIRE; Pentachlorophenol; Simazine